PENGEMBANGAN MODEL PELATIHAN IPTEKS BAGI KEWIRAUSAHAAN (IbK) UNTUK MENINGKATKAN KEMAMPUAN PENGELOLAAN BISNIS DIKALANGAN MAHASISWA - Nugraha Nugraha; Reni Amaranti; Aswardi Nasution (Teknoin, 2016)
Main discussion of this study is about the need proper entrepreneurship training program in higher education, especially for students, this study aims to acquire as well as to develop a proper entrepreneurial training model to improve ability of business management among students. The approach Model used in this study are ; 1) the development model of training science and technology for Entrepreneurship (IbK) , 2) model of Problem Based Learning (PBL) is one of the training strategy oriented contectual teaching and learning process (CTL) .The CTL  training concept helps the  trainers / instructors / teachers to links materials with real world situations as well as to encourage the participants  using their knowledge to be applied in their real life situation the members of society. From the training model implementation results, it can be concluded that: 1) The training model combining The Problem Based Learning (PBL) and the  development of  science and technology training model for Entrepreneurship (IbK )could be effectively applied in an  entrepreneurship training program for higher education level students, 2 ) This model succesfully synergize the materials / theories of the training to the real world situations ; 3) This model also works to build the teamwork. Finally, this model manage to indicate its effectiveness by the level of attendance at  90%, as well as teamwork formed in making innovative, original and worth-to-be implemented business proposal.